Video Surveillance in Portugal: political rethoric at the center of a technological project - Frois, Catarina (Social Analysis, 2011)
Serviços@b-on(opens in a new window)|Entitled full text(opens in a new window)|View at Publisher| Export | Download | Add to List | More... Social Analysis Volume 55, Issue 3, 2011, Pages 35-53 Video surveillance in portugal: Political rhetoric at the center of a technological project (Article) Frois, C. Research in Anthropology, Portugal View references (23) Abstract This article gives a detailed account of the political processes and stages involved in the implementation of video surveillance devices in two major Portuguese cities, Oporto and Lisbon. It seeks to draw two main conclusions regarding the introduction of these systems in public areas and the developments that they have undergone over the period under analysis. The first is that installing these devices reflects a political response designed to provide a hasty solution to a social phenomenon-fear-that is largely subjective. The second is that the generalized perception as to the uncertainty of the effectiveness of these systems explains the lack of consistency and coordination in their implementation. The article concludes by discussing fear and insecurity in the context of concerns for a more efficient justice system.